Domestic violence and abuse in local child safeguarding policy: How is the problem represented?. (25th October 2022) - Russell, Alexander; Clements, Keith; Duschinsky, Robbie; Howarth, Emma; Mayes, Tammy; Reisel, Alma; Coughlan, Barry
Abstract: Within the United Kingdom, domestic violence and abuse (DVA) is the most commonly identified factor within child in need assessments, with rates increasing in recent years in addition to 'lockdown'‐related spikes. This article examines the representation of DVA in local child safeguarding policies using Bacchi's (2009) 'What is the problem represented to be?' approach. Policies were collected from the websites of all the child safeguarding partnerships of England in July 2021. In total, we identified 59 policies. These policies are designed to guide local responses to DVA across services and thus have potential for substantial impact on practice across health and social care. Our results suggest that local DVA policy in England exists within a conceptual framework which spotlights the individual and lacks attention to their context. We argue that these policies focus on adults, neglecting attention to children within their own safeguarding policies. This is through children being peripheralized within the conceptualisation of 'victim' and the assessed adult risk being used as a proxy measure for the risk to child. Demographic discussions build an image of DVA as an issue that can affect anyone, but with little acknowledgement of the vulnerabilities facing proportions of the population and their complexities – when such vulnerabilities are discussed, they are individualised and viewed in absence of their societal causes, potentially eclipsing critical elements of a child's experience of DVA. The implications of our results are wide‐ranging but suggest a need to refocus on children and their context within local DVA policy.